(untitled) (Global Journal of Management and Business Research, 2023)
Purpose The emergence of Industry 4 0 has changed the way work is performed Supply Chain Management Professionals must adapt to these changes and develop skills needed for future work This study explores the impact of Industry 4 0 on the future skills of the supply chain management professionals with a focus on Saudi Aramco Methodology An integrative review approach was taken to synthesise the literature covering Industry 4 0 and the future of work skills Saudi Aramco s Supply Chain Professional Development Program was conducted and subsequently findings from the literature were discussed